Respiratory exposure to graphene oxide induces pulmonary fibrosis and organ damages in rats involving caspase-1/p38MAPK/TGF-β1 signaling pathways. (September 2022) - Kan, Ze; Zhao, Ke-Xin; Jiang, Chao; Liu, Da-Yang; Guo, Ying; Liu, Li-Yan; Wang, Wen-Juan; He, Zhi-Qiang; Zhang, Zi-Feng; Wang, Su-Yi
Abstract: Numerous studies have shown that graphene oxide (GO) respiratory exposure led to severe lung injury, but whether pulmonary fibrosis caused by GO respiratory exposure is related to the activation of the caspase-1/p38MAPK/TGF-β1 remains unclear. In this study, rats were administrated GO by intratracheal instillation and fed for three months, and the molecular mechanisms of GO on the pulmonary fibrosis and other organ damage caused by GO respiratory exposure were examined. The results showed that the expression of caspase-1/p38MAPK/TGF-β1 pathway-related factors were significantly elevated with the increase of exposure concentrations of GO. Those data proved that the caspase-1/p38MAPK/TGF-β1 signaling pathway was involved in the pulmonary fibrosis caused by GO respiratory exposure. The trends of related factors also proved that the caspase-1/p38MAPK/TGF-β1 pathway was likely to play a dominant role in the sub-acute and sub-chronic stages. The other organ damage examination found that the liver and spleen were damaged initially by the GO respiratory exposure. Meanwhile for the testicle, although the acute injury was severe, signs of recovery were found during the three-month trial period. Graphical abstract: Image 1 Highlights: The signaling pathways of pulmonary fibrosis caused by GO respiratory exposure. Acute and subacute responses to respiratory exposure to GO in rats. Damage to the liver, spleen, kidney and testicles due to respiratory exposure to GO. Reproductive damage caused by GO may be reversible.